Clinical features and outcomes of 20 patients with abdominopelvic desmoplastic small round cell tumor. Issue 2 (February 2017) - Angarita, F.A.; Hassan, S.; Cannell, A.J.; Dickson, B.C.; Gladdy, R.A.; Swallow, C.J.; Gupta, A.; Blackstein, M.E.; McCart, J.A.
Abstract: Introduction: Desmoplastic small round cell tumor (DSRCT) is a rare mesenchymal malignancy. We describe our experience with treating DSRCT at a large sarcoma referral center. Methods: A retrospective chart review was performed on DSRCT patients referred to our institution (1998–2014). Pathology specimens were reviewed to confirm the diagnosis. Clinical and imaging were extracted and summarized with descriptive statistics. Univariate analysis was performed to evaluate the association between patient, tumor, and treatment variables and overall survival (OS). Results: In this study cohort of 20 patients, median age at presentation was 29 y (range 18–43) and 90% were male. Fifty-five percent presented with metastasis. Patients underwent chemotherapy (n = 20), radiation therapy (n = 3), and cytoreductive surgery (CRS) (n = 5). Median OS was 22 m (interquartile range: 12–28 m). Five-year OS rate was 20%. Extra-abdominal metastasis was associated with a higher hazard ratio (HR) of mortality (HR: 3.1, 95% C.I. 1.0–9.4, p = 0.04), while CRS improved OS (HR: 0.1, 95% C.I. 0.03–0.7, p = 0.02). Conclusions: Despite aggressive treatment, less than half of the patients were dead of DSRCT within 2 years of presentation. Although a select group of patients who underwent CRS had improved OS, novel treatments are urgently needed.